2018
DOI: 10.3988/jcn.2018.14.2.141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex in Stroke Thrombolysis: A Systematic Review and Meta-Analysis

Abstract: Background and PurposeThere is increasing recognition of the importance of stroke in females to both clinical and public health. The natural course of stroke is worse in females than in males, but the evidence regarding sex disparities in the responses to thrombolysis in stroke patents is still controversial. We compared outcomes after thrombolysis treatment between females and males.MethodsClinical trials reported in the Embase, PubMed, and Cochrane Library electronic databases up to March 13, 2017 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
(112 reference statements)
1
23
0
Order By: Relevance
“…All patients without fibrinolytic treatment did not seem to vary their hospital improvement, while female seemed to get worse at discharge. Results are in line with a recent study on the influence of sex in stroke thrombolysis, where no relevant sex discrepancies were determined in outcome after intra-arterial thrombectomy (32).…”
Section: Discussionsupporting
confidence: 91%
“…All patients without fibrinolytic treatment did not seem to vary their hospital improvement, while female seemed to get worse at discharge. Results are in line with a recent study on the influence of sex in stroke thrombolysis, where no relevant sex discrepancies were determined in outcome after intra-arterial thrombectomy (32).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to invasive therapies, older studies have shown that women were less likely than men to receive thrombolytic therapy when admitted for ischemic stroke at both primary stroke centres and non‐primary stroke centres 20,21 . In some studies, females apparently exhibited a worse outcome than males after thrombolytic therapy, whereas no relevant sex differences were found in outcomes or recanalisation rates after endovascular thrombectomy 22 . However, later interaction studies have ruled out that sex can influence clinical outcomes after endovascular treatment for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Despite equal health-care access, literature has highlighted sex differences in management and outcome of cerebral [11] and cardiovascular [12,13] diseases. Moreover, delays in arrival to emergency departments probably explained why women had a reported lower rate of tPA treatment [14].…”
Section: Discussion/conclusionmentioning
confidence: 99%